Spint-Off: Peluang dan Tantangan Industri Asuransi Syariah di Indonesia - Lestari, Agustina Ayu; Yusuf, Mochamad; Kurniawati, Fitri (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
The development of sharia insurance certainly creates opportunities and challenges, because market penetration and spin-off efforts are required. This research aims to provide descriptive and explorative information about the potential and challenges of the Sharia insurance industry facing spin-offs. The research uses descriptive qualitative. This research uses a literature study. Data from secondary with technical analysis of reduction, validation, and concluding. The research results explain that the Sharia insurance industry has massive market penetration but has not responded well enough. The potential for sharia insurance through the spin-off process is to further increase effectiveness, quantity, and quality such as increasing units, more marketers, clear regulations, and increased literacy to the implementation of the spin-off policy. Spin-off is a solution for the Sharia insurance industry. This research contributes to the importance of awareness of spinoff opportunities as seen from the broad market prospects, policy support, small penetration, product heterogeneity, and lifestyle of Indonesians.